Field research 2012 - Kansas State University. Agricultural Experiment Station; Cooperative Extension Service (Kansas Agricultural Experiment Station Research Reports, 2012)
Includes research reports from these locations: East Central Kansas Experiment Field, Kansas River Valley Experiment Field, and Western Kansas Agricultural Research Centers.
Keywords: Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1066; Kansas Agricultural Experiment Station contribution; no. 12-293-S; Kansas; Agriculture; Crops; Disease control; Fertilizer; Irrigation; Weed control